Sex differences of COPD phenotypes in nonsmoking patients - Hong Y; Ji W; An S; Han SS; Lee SJ; Kim WJ (International Journal of COPD, 2016)
Yoonki Hong,1 Wonjun Ji,2 Soojeong An,3 Seon-Sook Han,1 Seung-Joon Lee,1 Woo Jin Kim1 1Department of Internal Medicine, Environmental Health Center, Kangwon National University Hospital, Chuncheon, South Korea, 2Department of Pulmonary and Critical Care Medicine, Asan Medical Center, University of Ulsan College of Medicine, Seoul, South Korea, 3Department of Statistics, Kangwon National University, Chuncheon, South Korea Background: There is growing evidence about sex-related phenotypes of COPD. However, the sex differences in COPD mainly result from smokers. This study evaluated the sex differences in nonsmoking patients with COPD, focusing on structural changes in the lungs in airway diseases and emphysema. Methods: Ninety-seven nonsmoking patients, defined as having <1 pack-year of lifetime cigarette smoking, diagnosed with COPD were selected from a Korean COPD cohort. Emphysema extent and mean wall area percentage (WA%) on computed tomography were compared between the male and female groups. Results: The 97 patients with COPD included 62 females and 35 males. Emphysema index was significantly lower (3.5±4.2 vs 6.2±5.7, P<0.01) and mean WA% on computed tomography was significantly higher (71.8%±5% vs 69.4%±5%, P<0.01) in females than in males, after adjusting for age, body mass index, history of biomass exposure, and postbronchodilator forced expiratory volume in 1 second (% of predicted). Conclusion: WA% was higher and emphysema extent was lower in nonsmoking females with COPD than in nonsmoking males with COPD. These findings suggest that males may be predisposed to an emphysema phenotype and females may be predisposed to an airway phenotype of COPD. Keywords: COPD, nonsmoker, emphysema, airway, sex